2016
DOI: 10.15253/2175-6783.2015000100002
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and characteristics of the nursing staff of a private hospital

Abstract: Objective: to analyze the relationships between sociodemographic/functional characteristics and the coping strategiesused by the nursing staff of a private hospital. Methods: it is a quantitative, analytical and cross-sectional study developedwith 209 nursing workers. Data were collected sociodemographic/functional characterization and form inventory of thecoping strategies. Results: positive reassessment, social support and problem solving were the most used coping factors.There was statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
8
0
6
Order By: Relevance
“…Similar results were also described in another study, in which coping scores were higher among professionals regarding health and work items, relating to lower stress scores, originating especially from the interpersonal work relations. 13 Data observed in the correlation of the coping questionnaire with that of stress showed a statistically significant positive association between coping and avoidance responses with all three stress factors. In a study carried out with intensive care nurses at a public hospital in Rio Grande do Sul, it was observed that the nurses face stress situations proactively in the work environment, that is, they promote cognitive reassessments about the stressors and how to respond to them.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similar results were also described in another study, in which coping scores were higher among professionals regarding health and work items, relating to lower stress scores, originating especially from the interpersonal work relations. 13 Data observed in the correlation of the coping questionnaire with that of stress showed a statistically significant positive association between coping and avoidance responses with all three stress factors. In a study carried out with intensive care nurses at a public hospital in Rio Grande do Sul, it was observed that the nurses face stress situations proactively in the work environment, that is, they promote cognitive reassessments about the stressors and how to respond to them.…”
Section: Discussionmentioning
confidence: 88%
“…11 In view of this, the person uses the coping mechanisms in an attempt to neutralize or eliminate the stress situation, either by facing it or moving away from it, but with the purpose of restoring their psychic balance. [12][13] Coping strategies can be divided into the following focuses: problem-centered coping and emotioncentered coping. 11 Regarding the first, it is sought to solve the situation through information about the stressful event and the analysis of an alternative action, in order to choose what is considered the most appropriate one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados obtidos nessa primeira etapa do estudo correspondem ao acúmulo de evidências de adequação dos procedimentos empregados por Balbinotti, Wiethaeuper e Barbosa (2013) para construção de um instrumento de avaliação de coping específico para atletas em situação de competição, uma vez que o instrumento apresenta estrutura fatorial semelhante àqueles que se pautaram na mesma compreensão/definição teórica (Holahan et al, 1996;Lazarus & Folkman, 1984;Zanini & Forns, 2014) para avaliação de coping em outros estratos populacionais, como adolescentes (Antoniazzi, 2000;Kristensen, Schaefer, & Busnello, 2010) e adultos (Benetti et al, 2015;Damião et al, 2009), bem como para avaliação de coping frente a situação específicas como a morte (Camarneiro & Gomes, 2015) e doenças oncológicas (Paula Junior, & Zanini, 2011;Rodrigues & Polidori, 2012). Dessa forma, pode-se inferir que o primeiro objetivo, estimar evidências de validade com base na estrutura interna do ICASC-40 (AERA; APA, & NCME, 2014), foi satisfatoriamente alcançado.…”
Section: Discussionunclassified
“…No entanto, apesar de serem importantes, avaliar as estratégias de enfrentamento ainda é uma tarefa complexa, principalmente quando o objetivo é identificá-las para, posteriormente, desenvolvê-las. Alguns autores trazem em seus estudos, instrumentos internacionais com esse objetivo, no entanto, também refletem acerca da carência de instrumentos com propriedades psicométricas adequadamente testadas no Brasil (Balbinotti, Barbosa, Wiethaeuper, & Teodoro, 2006;Benetti et. al., 2015;Camarneiro & Gomes, 2015;Damião, Rossato, Fabri & Dias, 2009).…”
unclassified